Reflections on death from the pandemic - Onaka Nuñez, Janina (2020)
The article tries to provoke a reflection on death as a result of the worldwide experience of the pandemic. Death has always been a mysterious subject and has generated various questions, but the superficiality in which we live today prevents, in many cases, from reflecting on the subject, which, however, must be done, since, from the answer we give the meaning of our life depends. In addition, it is convenient to be prepared because we do not know when we are going to die. It is, therefore, in this article, to highlight some aspects -paradoxical many of them- of death, a universal and necessary fact, although often forgotten, in order to live it in a personal way, with dignity and hope, in the specific situation of pandemic that we are going through. It is also about highlighting the value of the elderly and the family or, failing that, friendship, at the time of the last goodbye.